Moving from X to Xⁿ collaboration modes within organisational settings - Lala-Sides, Kaylarsh (University of Cape Town, 2020)
Organisations are increasingly dependent on the collaborative effort of individuals and teams to achieve outcomes such as solve complex problems, take advantage of opportunities and enhance organisational efficiencies. In fact, there are few activities that human beings are involved in which do not involve collaboration. Yet the experiences of individuals called upon to make collaborations work are often over-looked by leaders and collaboration conveners pre, during and post collaborations. These leaders tend to concentrate their attention on operational antecedents such as systems, processes and resources required, as well as the attainment of the collaboration outcome. It is therefore unsurprising that the outcome of collaborative activity is often capped at the specified outcome. However, in the context of a perform and outperform world and especially where global economic growth is severely contracted, there is ongoing interest in the ability of organisations to create competitive advantage through collaborativepeople- based advantage. The modern-day requirement is for collaboration activity to more accurately reflect the capabilities of the collaboration partakes. This study examines how individuals' self-efficacy, optimism, resilience, and trust influence how they collaborate within an organisation setting. Accordingly, the two primary areas of examination are collaboration and individuals' experiences. This phenomenological and explorative study adopted an inductive, qualitative, single-case study approach adopting interviews, questionnaire, observation and secondary data as research instruments. The study was conducted with a mature non-profit organisation where collaboration was identified as crucial to the attainment of their goals and targets. A review of the evolution of collaboration as a theory in its own right was conducted as part of the study. The field of positive psychology and in particular the offshoots of positive organisation behaviours and positive psychological capabilities were reviewed as the foundation from which individuals' experiences were examined within the study. The study revealed that while individuals' experiences were considered important by the leaders within the case examined, they were largely ignored during collaboration efforts. As a result, individuals' experiences were not considered important inputs to collaboration efforts. Furthermore, individuals' experiences were not considered influential to the attainment of collaboration outcomes nor to the attainment of specified organisational targets and goals. In particular, optimism and trust were found to markedly contribute to individuals' experience during a collaboration, while self-efficacy and resilience did so to a lesser degree. Interestingly, rapid organisation growth emerged as an unanticipated yet key influencer to individuals' experiences during collaboration. The study makes a threefold contribution. The first is theoretical contribution to collaboration theory by exposing the positive and negative, external and internal antecedents of individual's experiences during collaboration. The applicable experience construct (self-efficacy, optimism, resilience, trust and growth as an influencer), or a combination thereof, as found in this study, is mapped out for each antecedent type in the "Framework for Individual's Experiences during Collaboration". The framework also includes the positive and negative, individual level and organisational level outcomes of individual's experiences. Thus, in so doing, the second contribution made is to the continually expanding research of Psychological Capabilities (PsyCap) and the specific outcomes they influence. The third contribution of this study is the development of the "Xⁿ collaboration model" which depicts three modes of collaboration where each mode influences the outcome and performance of an organisation against its identified objectives.